A methodology on stocktaking of gender-responsive policies and measures during COVID-19 in Ethiopia, Senegal and Zambia - CGIAR GENDER Platform (2021)
The methodology was used in a qualitative study on stocktaking of gender-responsiveness measures by governments and development agencies in Ethiopia, Senegal and Zambia. Its findings informed discussions during a policy dialogue on 16 November 2021, development of 3 country reports, 3 policy briefs, a video and an overview report.